Music as a teaching language: experience report on the use of Luiz Gonzaga's work - de Farias, Henrique Silveira; de França, Dhayanna Chrystian Silva; de Andrade, Bruno Vieira (Revista Ensino de Geografia (Recife), 2019)
This job was made based on the final paper titled “The music as language to Geography Teaching: an analysis over Luiz Gonzaga’s songs”, written by Henrique Silveira, one of the authors of this article. The final paper consisted in an analysis of the song of Luiz Gonzagaand from that point out which songs could serve as support to Geography classes. Further, a group of teachers of Geography, History, Biology, and Portuguese from a private school from Recife (State of Pernambuco) elaborated a “aulão” to 9thGrade and Highschoolers students, aiming to solve some exams questions and discuss about various themes around the Northeast Region. The teachers used Luiz Gonzaga’s songs as a tool to help the question solving, where the music was played live in the “aulão”. This present job tells the experience of the utilization of musicas teaching language over Luiz Gonzaga’s work.